Undergraduate university students mentoring program: experiences of mentors and mentees - Al-Aqeel, Sinaa; Alhumaid, Hana Khalid (Frontiers in Education, 2024)
IntroductionResearch on the impact of mentoring on students and mentors is limited. Therefore, this study explored the experiences of mentors and mentees involved in a mentoring program for undergraduate students at a governmental academic institution in Saudi Arabia. The program connected undergraduate students with peer students, academic staff, or alumni based on their needs.MethodsUsing an online survey (n = 80) and a focus group (n = 24), we examined mentees and mentors' perceptions of their mentoring experiences. Descriptive statistics were used to summarize participants' responses to the survey. The focus group data were analyzed using six phases of thematic analysis.Results and discussionThe findings showed that the participants' mentoring experience was positive, with some challenges, such as limited time, unmet expectations of mentees, and a lack of student engagement. The motivation to volunteer as a mentor focused mainly on wanting to help others and appreciating the value of mentoring based on the mentors' previous experiences.